SPATIAL ANALYSES OF WIND SPEED IN THE NORTH-BRAZIL WITH DATA FROM ERA-40 - SANTANA, Lêda Valéria Ramos; STOSIC, Tatijana; DEZOTTI, Cláudia Helena; MOURA, Geber Barbosa de Albuquerque; ARAÚJO, Luiz Henrique Gama Dore de; SILVA, Antonio Samuel Alves da (Brazilian Journal of Biometrics, 2015)
In this work were analyzed daily time series of wind speed in northeastern Brazil. The data were obtained through the ERA-40 reanalysis for the period 1958-2001 in order to verify which of the probability distribution, Weibull, Gamma and Generalized Rayleigh, better describes the probabilistic behavior of the wind speed in the region. In this sense, were performed spatial analyzes by using the inverse distance weighting for the p-value and the estimated parameters. The Weibull distribution of two parameters was that best represented the distribution of wind speed in most Brazilian NE and the Forest Zone region represented the highest rate and the lowest wind speed variability.